Ovarian preservation in adenocarcinoma of the uterine cervix - Jiansong Zhou; Yuanyuan Chen; Ping Zhang; Hanmei Lou (BMC, 2017)
Abstract Background An upward trending incidence in cervical adenocarcinoma (ADC) has been reported in many countries. Because non-squamous histology has been associated with increased risk of ovarian metastases (OM), bilateral oophorectomy is commonly performed for ADC without due consideration for ovarian preservation, degrading the quality of life for young premenopausal patients. Methods Subjects were patients with International Federation of Gynecology and Obstetrics (FIGO) stage I-IIB cervical ADC who underwent radical hysterectomy, including pelvic lymphadenectomy and bilateral salpingo-oophorectomy at our institution between Oct. 2006 and Sept. 2014. Clinicopathologic variables were studied by univariate and multivariate analyses. Results Of the 312 patients enrolled in the study, 14 patients (4.5%) developed OM. Multivariate analysis revealed that uterine corpus involvement (odds ratio [OR] 5.178, p = 0.019), parametrial involvement (OR 14.125, p = 0.005) and vaginal infiltration (OR 4.167, p = 0.047) were independently associated with metastasis. OM had no effect on either relapse-free survival (95% confidence interval [CI]: 0.077-4.095, p = 0.57) or overall survival (95% CI: 0.893-9.820, p = 0.076). Conclusion Cervical ADC is associated with an increased risk of OM. Ovarian preservation surgery in cervical ADC may be safe for young patients at an early FIGO stage without deep stromal, endometrial or perineural invasion, and particularly without uterine corpus invasion, parametrial involvement and infiltration into the vagina.